A Randomized Controlled Trial on the Effects of a 12-Week High- vs. Low-Intensity Exercise Intervention on Hippocampal Structure and Function in Healthy, Young Adults - Kaiser, Antonia; Reneman, Liesbeth; Solleveld, Michelle M.; Coolen, Bram F.; Scherder, Erik J. A.; Knutsson, Linda; Bjørnerud, Atle; van Osch, Matthias J. P.; Wijnen, Jannie P.; Lucassen, Paul J.; Schrantee, Anouk (Frontiers in Psychiatry, 2022)
Physical exercise affects hippocampal structure and function, but the underlying neural mechanisms and the effects of exercise intensity remain incompletely understood. Therefore, we undertook a comprehensive, multi-modal 3T and 7T MRI randomized controlled trial (Netherlands Trial Register - NL5847) in which we randomized 52 young, non-athletic volunteers to a 12-week low- or high-intensity exercise program. Using state-of-the-art methods, we investigated changes in hippocampal volume, as well as changes in vasculature, neuro-metabolites, and peripheral growth factors as potential underpinnings. Cardiorespiratory fitness improved over time (p<0.001), but no interaction with exercise intensity was found (p=0.48). Accordingly, we did not observe significant interactions between exercise condition and time on MRI measures (all p>0.02). However, we found a significant decrease in right hippocampal volume (p<0.01), an increase in left hippocampal glutathione (p<0.01), and a decrease of left hippocampal cerebral blood volume (p=0.01) over time, regardless of exercise condition. Additional exploratory analyses showed that changes in brain-derived neurotrophic factor (p=0.01), insulin-like growth-factor (p=0.03), and dorsal anterior cingulate cortex N-acetyl-aspartate levels (p=0.01) were positively associated with cardiorespiratory fitness changes, additionally, a trend towards a positive association of fitness and grey-matter cerebral blood flow (p=0.06) was found. Our results do not provide evidence for differential effects between high-intensity (aerobic) and low-intensity (toning) exercise on hippocampal structure and function in young adults. However, we show small but significant effects of exercise on hippocampal volume, neurometabolism and vasculature across exercise conditions. Moreover, our exploratory results suggest that exercise might not specifically only benefit hippocampal structure and function, but rather has a more widespread effect.These findings suggest that in agreement with previous MRI studies, demonstrating moderate to strong effects in elderly and diseased populations, but none to only mild effects in young healthy cohorts, the benefits of exercise on the studied brain measures may be age-dependent and restorative rather than stimulatory. Our study highlights the importance of a multi-modal, whole-brain approach to assess macroscopic and microscopic changes underlying exercise-induced brain changes, to better understand the role of exercise as a potential non-pharmacological intervention.